EFL Writing Studies in Colombia Between 1990 and 2020: A Qualitative Research Synthesis - María Eugenia Guapacha Chamorro; Orlando Chaves Varón (Profile: Issues in Teachers' Professional Development)
This article provides a comprehensive qualitative synthesis of EFL writing studies published in Colombian journals between 1990 and 2020. We synthesised 63 research reports regarding authorship, publication year, focus, methodology (context, participants, research paradigm, design, and data collection methods and analyses), validity, reliability, ethics, findings, limitations, and further research. Our findings reveal that EFL writing is a developing research area in Colombia, characterised as a predominantly qualitative inquiry into adult writing instruction and learning at universities. From the findings, we propose a research agenda and some guidelines for authors and reviewers to enhance and evaluate research reports.